A sensor-less methanol concentration control system based on feedback from the stack temperature - An, Myung-Gi; Mehmood, Asad; Ha, Heung Yong (ELSEVIER SCI LTD, 2014)
A sensor-less methanol concentration control system based on feedback from the stack temperature (SLCCF) has been developed. The SLCCF algorithm is embedded into an in-house LabVIEW program that has been developed to control the methanol concentration in the feed of direct methanol fuel cells (DMFCs). This control method utilizes the close correlation between the stack temperature and the methanol concentration in the feed. Basically, the amounts of methanol to be supplied to the re-circulating feed stream are determined by estimating the methanol consumption rates under given operating conditions, which are then adjusted by a proportional-integral controller and supplied into the feed stream to maintain the stack temperature at a set value. The algorithm is designed to control the methanol concentration and the stack temperature for both start-up and normal operation processes. Feasibility tests with a 200 W-class DMFC system under various operating conditions confirm that the algorithm successfully maintains the methanol concentration in the feed as well as the stack temperature at set values, and the start-up time required for the DMFC system to reach steady-state operating conditions is reduced significantly compared with conventional sensor-less methods. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: FUEL-CELL SYSTEM; DMFC; PERFORMANCE; LOAD